Symmetry analysis, soliton solutions and conservation laws of the Q(L, m, n) equation - Wang, Gangwei; He, Mengyue; Zhou, Qin; Kara, Abdul H. (Nonlinear Analysis: Modelling and Control, 2025)
In the present paper, symmetry and soliton solutions of the Q(L, m, n) equation are investigated. The infinitesimal operator of this equation is obtained by virtue of Lie group analysis. Taking different values of the parameters for the coefficients, the corresponding vector fields are obtained. Subsequently, soliton solutions of this equation are obtained for different parameters relying on the solitary wave ansatz method. According to different parameters, new soliton solutions are obtained. Also, conservation laws are also derived. Reciprocal Bäcklund transformations of conservation laws presented from the known conservation laws.